Long-term development of Born Global Firms. Entrepreneurial orientation and innovative culture in Italian Born Globals - Corredato, Camilla (My University, 2018)
Due to the rise of international operations during the past thirty years, Born Global firms have been caught the attention of many scholars since their rising. In the existing literature there are different definitions of Born Globals, this proved that they represent an important topic in the international business filed. Every aspect of Born Globals has been analysed: the triggers that pushed the internationalisation process at the beginning and the performances during the short-term. What was very little addressed were the performances during the long-term, in particular for what concerns the Entrepreneurial Orientation and the Innovative Culture. The two aspects are addressed in the following study. More specifically, the Italian business environment is taken into account due to the strong presence of young small and medium enterprises that internationalise their business operations since inception. Based on the previous studies it is built a theoretical framework in order to investigate the Entrepreneurial Orientation and the Innovative Culture during the long-term development of Born Global firms in the Italian business environment. In order to achieve the theoretical purpose, above mentioned, in the study are investigated firstly the triggers that pushed Italian Born Globals to internationalise their activities, secondly, the performances in the short-term are considered to better understand the strategies that those firms adopted. Thirdly, the elements that could affect the long-term performances are considered in order to detect the importance of Entrepreneurial Orientation and Innovative Culture during the long-term development. The study is based on the analysis of firms’ behaviour toward the long-term development of the internationalisation strategies in order to detect how the performances are influenced by the Entrepreneurial Orientation and the Innovative Culture. Three semi-structured interviews among Italian Born Globals were conducted in order to better evaluate their attitude in facing foreign markets by exploiting the prior experience and knowledge of the founders to face the risk. In addition, the interviews helped the researcher to investigate the organisational learning culture that leads to Innovative Culture within a firm. The findings proved that the Entrepreneurial Orientation and Innovative Culture do not change during the long-term development of a Born Global, indeed they are the key elements to maintain a successful positioning in foreign countries.
Keywords: Born Global Firms; Entrepreneurial Orientation; Innovative Culture; Long-term Development; International Development; Fast Growing Firms; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|; fi=Organisaatioiden viestintä|en=Communication in organizations|